Firearm injuries associated with law enforcement activity. (October 2021) - Loder, Randall T.; Young, Allison; Atoa, Bradley
Abstract: Background: Law enforcement activity can involve firearms, and either a civilian or the law enforcement officer can be injured. It was the purpose of this study to characterize the injuries and demographics associated with law enforcement firearm activity across the entire US using a national data base. Methods: Inter-University Consortium for Political and Social Research Firearm Injury Surveillance Study data 1993–2015 was used. Law enforcement involvement and other demographic variables were ascertained. Statistical analyses were performed accounting for the weighted, stratified nature of the data. P < 0.05 was considered to be statistically significant. Results: There were an estimated 2, 667, 896 ED visits for injuries due to firearms; 1.7% (45, 497) were associated with law enforcement. Those involved with law enforcement were older (33.2 vs 29.8 years), a handgun was more commonly involved (80.3 vs 71.5%), male (90.7 vs 86.8%), White (52.9 vs 37.2%), had more upper trunk injuries (25.2 vs 16.2%), fewer lower extremity (15.1% vs 25.9%) injuries, and more fatalities (10.0 vs. 6.2%). An argument, crime, fight and drug involvement were all greater in the law enforcement group. Within the law enforcement group, when the injured patient was the civilian and not the officer, the patient was more commonly Black, male, sustained more trunk injuries, fewer extremity injuries, and more frequently admitted to the hospital. The civilian group had fewer upper extremity (11.7% vs 29.7%), lower extremity (12.2% vs 23.7%) and lower trunk injuries (14.6% vs 8.0%), more upper trunk injuries (31.3% vs 7.8%, and similar proportion of head/neck injuries (31.5% vs 30.7%) compared to the officer group. More females were injured in the officer group (16.9% vs 7.5%). The fatality rate was 12.6% for the civilian group and 3.0% for the officer group. There were no differences by race in disposition from the ED (released, admitted, death) for those who sustained injuries by the officer. Conclusions: Firearm injuries due to law enforcement activity occurred in 1.7% of all ED visits for injuries due to firearms. The law enforcement officer was the injured patient in 23% of the events. This study spanning nearly a quarter of a century of data for injuries due to firearm activity resulting in ED visits is baseline data for future studies, especially in the present setting of calls for police reform within the US. This will be important when analyzing the effect of new programs in law enforcement training and/or police reform.